2013
DOI: 10.1111/epi.12241
|View full text |Cite
|
Sign up to set email alerts
|

An SCN2A mutation in a family with infantile seizures from Madagascar reveals an increased subthreshold Na+ current

Abstract: SUMMARYMissense mutations in SCN2A, encoding the brain sodium channel Na V 1.2, have been described in benign familial neonatal-infantile seizures (BFNIS), a self-limiting disorder, whereas several SCN2A de novo nonsense mutations have been found in patients with more severe phenotypes including epileptic encephalopathy. We report a family with BFNIS originating from Madagascar. Onset extended from 3 to 9 months of age. Interictal EEGs were normal. In two patients, ictal electroencephalography (EEG) studies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 11 publications
(17 reference statements)
2
48
1
Order By: Relevance
“…For the p.(Lys908Glu) variant, we found a significantly increased sodium inward current, which occurred only in the critical subthreshold depolarizing phase of an action potential ( I NaS ). This phenomenon was first observed in Na V 1.2 channels for the BFNIE‐causing variant p.(Tyr1589Cys), which additionally showed a depolarizing shift of steady‐state inactivation, an increased I NaP , a slowing of fast inactivation and an acceleration of its recovery (Lauxmann et al., ). The nature of this subthreshold current is still unclear.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For the p.(Lys908Glu) variant, we found a significantly increased sodium inward current, which occurred only in the critical subthreshold depolarizing phase of an action potential ( I NaS ). This phenomenon was first observed in Na V 1.2 channels for the BFNIE‐causing variant p.(Tyr1589Cys), which additionally showed a depolarizing shift of steady‐state inactivation, an increased I NaP , a slowing of fast inactivation and an acceleration of its recovery (Lauxmann et al., ). The nature of this subthreshold current is still unclear.…”
Section: Discussionmentioning
confidence: 87%
“…So far, more than 140 different SCN2A variants and more than 7 chromosomal aberrations have been identified with a broad range of the phenotypic spectrum. Within those, only 25 different variants (including the three here studied variants) in the adult and neonatal splice variants have been electrophysiologically characterized until now (Table ), four of which were classified as LoF variants (Kamiya et al., ; Liao, Anttonen, et al., ; Liao, Deprez, et al., ; Ogiwara et al., ; Scalmani et al., ; Schwarz et al., ; Sugawara et al., ; Sugawara et al., ; Wolff et al., ), 15 as GoF variants (Lauxmann et al., ; Wolff et al., ; Xu et al., ), and as a combination of LoF and GoF variants (Ogiwara et al., ). Three variants (p.(Arg1319Gln), p.(Leu1330Phe) and p.(Leu1563Val)) exhibited a significant reduction in cell surface expression (Misra et al., ) predicting a net decrease in channel activity.…”
Section: Discussionmentioning
confidence: 99%
“…If this hypothesis were correct, we would expect the missense variants observed in ASD to reduce Na V 1.2 channel function and decrease neuron excitability. We therefore performed functional analyses of all 12 de novo SCN2A mutations observed in the 4,109 ASD cases from the Simons Simplex Collection (SSC; 2,508 families with a single affected child) and Autism Sequencing Consortium (ASC; 1,601 families with one or more affected children), as these cases were identified as representing idiopathic ASD in clearly defined cohorts (4, 9, 22). …”
Section: Resultsmentioning
confidence: 99%
“…More than 30 Na v 1.2 mutations have been discovered and some of them are now functionally characterized. Interestingly, electrophysiological studies showed that Na v 1.2 mutations can either be loss-of-function (R1319Q and L1330F) or gain-of-function (M252V, V261M, L1563V, and Y1579C) (Misra et al, 2008; Liao et al, 2010; Lauxmann et al, 2013). It is noted that BFIS3 mutations in Na v 1.2 create less pronounced changes in the activation and inactivation potentials than the EIEE11 mutations (Shi et al, 2012).…”
Section: Mapping Of Other Human Sodium Channel Disease-related Mutatimentioning
confidence: 99%